‘The Catholic Church and Condoms’: His Eminence Alfonso Lopez Cardinal Trujilo appears on ‘BBC Panorama’ in 2003 and 2004 - Hutchings, Patrick FitzGerald (Sophia, 2004)
The Theological Consequence is of a more scandalous nature for Catholic ‘insiders’—the literate laity etc.etc.—than is the ‘mere’ ‘Humanist’ one. The pair together can to ‘Evangalisation’ no good at all., The Eminence, who on the BBC programme looks slightly comic. is, when one reflects a very disquieting figure indeed. So: A squib is comic: a serious one is, serious., Note the ‘BBC Panorama’ presentations have been seen in Australia, and so, possibly, in other countries in which this Journal is read.